Role of Intellectual Property Rights in promoting ecotourism in Sri Lanka - Hirimuthugodage, Dilani (Journal of International Economics and Management, 2016)
Tourism sector in Sri Lanka is the third largest foreign exchange earner to the country which recorded nearly 1.5 mil. tourist arrivals in 2014, whereas Asia appeared as the main tourism source followed by Western Europe. Employment generation both direct and indirect through the tourism sector is quite significant, where it directly provide nearly 130,000 employment opportunities every year. According to the World Tourism Organization, ecotourism is recorded as the highest growing market in the tourism industry with an annual growth rate of 5 per cent worldwide. Nearly 3 percent of international tourist visits to Sri Lanka comprises of eco tourists, making ecotourism an emerging market in the country. Sri Lanka has notable ecotourism resources and the government institutes are responsible in promoting ecotourism. The Intellectual Property Rights (IPRs) which includes patents, trademarks, sui generis system, geographical indications, industrial designs, traditional knowledge etc. are some of the important IPRs in developing and promoting ecotourism. Although Sri Lanka passed its IPR Act in 2003, thus far IPRs are not widely used in Sri Lankan tourism sector including ecotourism. The overall objective of this paper is to identify strategies to promote ecotourism by strengthening IPRs in Sri Lanka. The specific objectives are to; identify types of IPRs that Sri Lankan ecotourism is currently using, evaluate present IPR system in tourism more particularly in ecotourism, identify international best practices in using IPRs to promote ecotourism and propose suitable strategies for proper use of IPRs in promoting ecotourism. The methodology of the study consists of a comprehensive literature survey, country case studies and in-depth interviews with main stakeholders. The findings highlighted the importance of disseminating knowledge on the importance of IPRs and the use of IPRs in protecting biodiversity, culture, traditional knowledge etc. in ecotourism to the grass root levels. It is important to provide a platform for stakeholders to discuss matters and to provide feasible strategies in protecting biodiversity, culture and traditional knowledge while promoting ecotourism. Further, it is essential to establish a separate unit to monitor and to provide adequate information and support in exploiting IPRs in ecotourism.